Rofel Brion Recalls and Reimagines the Creative Writing Program - Villanueva, Martin V (Archīum Ateneo, 2021)
As of this writing; only Rofel Brion and I have served as coordinators of the BFA Creative Writing program under the Department of Fine Arts. Although I am a graduate of the program he cofounded; we’ve never had a conversation about the program. Since Rofel’s time as its coordinator; the program has grown (and; hopefully; grown up a bit too) to having over 20 graduating students and a total of more than 150 majors across four year-levels in 2021; a year before the twentieth anniversary of the pilot batch of three. Rofel has done other and more significant things for Ateneo and in literature; and the CW program is but a small and relatively recent plot point in the story of Ateneo writing. But I thought I’d take advantage of the festschrift to finally speak to Rofel about the program and his perspectives on mentoring creative writing students.